THE VOICE OF MEMORY: ORAL HISTORY, COUNTRY MUSIC AND INTANGIBLE HERITAGE IN THE EXPERIENCE OF THE ELDERLY - Elias Garcia, Tatiane (Revista Gênero e Interdisciplinaridade, 2024)
This article explores the intersection between oral history, country music, and intangible heritage, with an emphasis on the experiences of the elderly. Using oral history as a methodology, we seek to understand how the personal narratives of the elderly contribute to the preservation and transmission of country culture. We analyze country music not only as an artistic expression, but also as a vehicle for collective memory and cultural identity. We highlight initiatives such as the Memórias Vivas Project in Piracanjuba, which promote intergenerational dialogue and strengthen community ties. We conclude that valuing the voices of the elderly is essential for the maintenance and revitalization of Brazil's intangible cultural heritage.